SOCIO-PSYCHOLOGICAL ASPECTS OF MOTIVATION TENDENCIES IN THE PROFESSIONAL ACTIVITIES OF A TEACHER IN THE CONDITIONS OF WAR: A COMPARATIVE ANALYSIS - Bilozerska, Svitlana; Mashchak, Svitlana (European Science, 2025)
The study characterizes the theoretical motivational trends of the professional activity of teachers with different experience of professional pedagogical activity in war conditions. It is stated that motivational trends in the demand-motivational sphere